UTILIZATION OF LEARNING MEDIA ON SCIENCE MATERIALS AS LEARNING RESOURCES IN ELEMENTARY SCHOOLS - Ni Made Mega Hariani (STAH Dharma Sentana Sulawesi Tengah, 2023)
This study aims to describe the use of learning media and to find out the obstacles to using learning media in science material as a learning resource in elementary schools. This type of research is a type of qualitative research with a descriptive approach. Data collection techniques are observation, interviews and documentation. The research results obtained are the use of learning media on natural science material as a learning resource at SD BK Lekatu has utilized learning media in teaching and learning activities, especially in science material, the media is used as an intermediary in delivering material so that it is easier and the material is more quickly understood by students. The media used by the teacher in learning science material at SD BK Lekatu are: white boards, concrete objects, models or artificial media, projectors and LCDs, videos, pictures, and print media. The stages of using learning media in science material were carried out by teachers at SD BK Lekatu, starting from planning, implementing, and evaluating. Obstacles in the use of learning media in science material at SD BK Lekatu are limited media, lack of knowledge, skills, creativity, and teacher time, and teachers feel comfortable with other methods